Genitourinary Reconstructive Surgery Curriculum and Postgraduate Training Program Development in the Caribbean - Jessica DeLong; Ramon Virasoro (Société Internationale d’Urologie Journal)
ObjectivesTo describe the development of a genitourinary reconstructive fellowship curriculum and the establishment of the first genitourinary reconstructive and pelvic floor postgraduate training program in the Caribbean. MethodsIn an effort to respond to the need for specialty-trained reconstructive urologists in the Dominican Republic, we developed an18-month fellowship program to train local surgeons. The process began with creation of a curriculum and partnership with in-country physicians, societies, hospitals, and government officials. We sought accreditation via a well-established local university, and fellowship candidates were selected. A database was maintained to track outcomes. Subjective and objective reviews were performed of the fellows. ResultsThe first fellow graduated in 2018, the second in 2020, and the third is currently in training. The curriculum was created and implemented. The fellowship has been successfully integrated into the health system, and the fellows performed 199 and 235 cases, respectively, during the program, completing all rotations successfully. They have been appointed to the national health system. Both graduates are now docents in the program and in the public system. Additional staff including radiologists, radiology technicians, nurses, urology residents (both Dominican and American), urology attendings, operating room staff, and anesthesia residents were trained as a result of the program. ConclusionsTo our knowledge, this is the first fellowship of its kind in the Caribbean. A novel curriculum was created and implemented, and the first 2 fellows have successfully completed all rotations. This training model may be transferable to additional sites